Effect of Disposable Income on Life Insurance Demand in Sub-Sahara Africa: Array - Osamwonyi, Ifuero; Iyawe, Osama (Acta Universitatis Danubius. Œconomica, 2021)
Abstract This study examines the effect of disposable income on life insurance demand in Sub-Sahara Africa by taking a sample of 15 selected African countries in the Sub-Sahara region. To achieve this, we selected various countries that have consistently published their data between 1995 and 2016. It is proposed in this study that the key macroeconomic factors driving life insurance demand in the case of Sub-Sahara Africa is disposable income captured by GDPPC. The modelling adopted in this study categorises all the necessary macroeconomic factors in the study that seek to explain both insurance density and penetration for the sampled countries which are South Africa, Ghana, Cameroon, Nigeria, South Africa, Cote I’dvoire, Sudan, Kenya, Mozambique, Uganda, Benin, Togo, Cape Verde, Senegal and Zambia. The study adopted a panel (balanced) data analysis to identify country - specific type of disposable income and how it affects life insurance demand. To this end, unit root test analysis was done to check the level of stationarity in the specified models. Keywords: Gross Domestic Product Per Capita, Inflation, Disposable Income, Interest Rate, Life Insurance Demand JEL Classification: G22, G5, G52.